Che on My Mind - Randall, Margaret, 1936- (Book collections on Project MUSE., 2013)
"Che on My Mind "is an impressionistic look at the life, death, and legacy of Che Guevara by the renowned feminist poet and activist Margaret Randall, who participated in the Mexican student movement of 1968 and was eventually forced to leave the country. She arrived in Cuba in 1969, less than two years after Che's death, and lived there until 1980. She became friends with several of Che's family members, friends, and compatriots. In "Che on My Mind" she reflects on his relationships with his family and fellow insurgents, including Fidel Castro. She is deeply admiring of Che's integrity and charisma and frank about what she sees as his strategic errors. Randall concludes by reflecting on the inspiration and lessons that Che's struggles might offer early twenty-first-century social justice activists and freedom fighters